Seasonal reproductive patterns of early domestic sheep at Tell Halula (PPNB, Middle Euphrates Valley): Evidence from sequential oxygen isotope analyses of tooth enamel. (April 2016) - Tornero, C.; Balasse, M.; Molist, M.; Saña, M.
Abstract: Sheep were adopted at Tell Halula site during Late PPNB (ca. 7500 cal BC). Shortly thereafter, sheep increased and became one of the main animal resources in this site. Previous studies have shown that planning of reproductive strategies of these early domesticated sheep involved selection of already-domestic rather than wild specimens to mold new herds, and that demographic management favored sexually mature females. In this study we investigate the seasonal reproductive pattern of sheep from Tell Halula site and determine if manipulation of birth seasonality played a role in the adoption and management of the species. Sequential stable isotope analyses of δ 18 O in tooth enamel bioapatite show that sheep were mainly born within a period of ca. 2.5 months. This duration of birth period is very similar to that observed in modern mouflon populations and to some of the ethnographic record for domestic herds from the study area. Data suggest that the reproductive pattern of early domesticated sheep was still, in the area of study, under strong environmental constraints; although at the moment is not possible to elucidate whether this synchronicity was intentional. Highlights: Seasonal reproductive pattern of sheep from Tell Halula (Late PPNB, Syria) is investigated. Potential manipulation of birth seasonality in adoption and early management of sheep is evaluated. Sequential stable isotope analyses of δ 18 O were performed in tooth enamel bioapatite. Sheep were mainly born within a period of ca. 2.5 months. Data suggest that the reproductive pattern of early domesticated sheep was still under strong environmental constraints.